Local Resection of Giant Cell tumor of Distal Radius and Re-construction by Fibular Autograft (Journal of Pakistan Orthopaedic Association, 2014)
Background: Giant cell tumour of the bone (GCT) is a benign but locally aggressive neoplasm accounting for 4% to 9.5% of all bone tumours. In our setup patients present at a late stage, so treatment has to be tailored on an individual basis weighing risk of recurrence versus function.Objective: To explore the union rate and restoration of range of movement after resection of giant cell tumour of distal radius and reconstruction by proximal fibular auto graft. Subjects &Methods: After informed consent, using purposive non-probability sampling, eight patients of either sex with age ranging from 16 to 40 years with histologically proved giant cell tumour of distal radius were included. All the tumours were well contained within an intact cortex. All the patients underwent wide local excision of tumour and reconstruction with ipsilateral proximal fibular autograft.Results: Eight patients were included in the study, mean age of the patient was 18.3 Â± 7.5 years; seven patients (87.5%) achieved union during post-operative period of six months. Satisfactory range of movement was achieved however flexion and adduction was restricted as compared to extension and abduction.Conclusion: It is concluded that wide resection and reconstruction by proximal fibular autograft for giant cell tumour of the distal radius is an acceptable procedureKeywords: Bone graft, Giant cell tumour, Wide resection, Autograft